Pengaruh Iklan, Promosi, dan Diskon Terhadap Ketertarikan Nasabah Dalam Bertransaksi Menggunakan Mesin EDC Merchant Pada PT Bank Rakyat Indonesia (Persero) Tbk Cabang Madiun - Rizki Wakid Khasbulloh; Hartirini Warnaningtyas; Choirum Rindah Istiqaroh; Samsu Anhari Faujianto (Universitas Merdeka Madiun, 2023)
This study aims to determine the effect of advertising, promotion, and discounts on customer interest in making transactions using the EDC merchant machine owned by PT Bank Rakyat Indonesia Madiun Branch, either partially or simultaneously. This type of research is quantitative research. The population in this study are customers of PT Bank Rakyat Indonesia Madiun Branch. While the sample in this study were 96 people. The sampling technique is purposive sampling. Data obtained from questionnaires. Data analysis used multiple linear regression analysis, classical assumption test, coefficient of determination, t test and F test. The results showed that there was a partial and simultaneous influence of advertisements, promos and discounts on customer interest in transacting using the merchant's EDC machine owned by PT. Bank Rakyat Indonesia Madiun Branch. Advertisements, promos and discounts can customer interest for making transactions using EDC merchant machines by 92.1%.